BI-OBJECTIVE AGE-BASED PRODUCTION-DISTRIBUTION PLANNING FOR PERISHABLE PRODUCTS - Alipour, Zohreh; Jolai, Fariborz; Zaerpour, Nima; Monabbati, Ehsan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2020)
Supply chain management of perishable products especially fresh food is different from other types of products because of extraordinary amount of wastage during inventory holding in facilities and transportation process. With considering production and distribution planning simultaneously waste costs will probably be reduced. Although, a lot of integrated production-distribution planning models were presented, an integrated model with considering fresh food specifications in objective functions and constraints is still needed. In this paper, we present a multi-objective age-based integrated production-distribution planning model. Our focus is on perishable products particularly fresh food and fresh products. The proposed model is of integer linear programming type that aims to minimize simultaneously sum of the production, inventory holding, wastage costs and sum of the freshness related costs and transportation costs. The balanced box method is applied to find non-dominated solutions for the proposed bi-objective model. Numerical experiments are conducted to evaluate the applicability and validity of the proposed model. Our results show that fresh products related specifications must be taken into account in the objective and constraints simultaneously